QCD sum rule study for a possible charmed pentaquark Θ c(3250) - Albuquerque, Raphael M. [UNESP]; Lee, Su Houng; Nielsen, Marina (American Physical Society (APS), 2013)
We use QCD sum rules to study the possible existence of a Θc(3250) charmed pentaquark. We consider the contributions of condensates up to dimension 12 and work at leading order in αs. We obtain mΘc=(3.29±0.13) GeV, compatible with the mass of the structure seen by BABAR Collaboration in the decay channel B-→p̄Σc++π-π-. The proposed state is compatible with a previous proposed pentaquark state in the anticharmed sector. © 2013 American Physical Society.